Susceptible period of socio-emotional development affected by constant exposure to daylight. (April 2015) - Koshiba, Mamiko; Senoo, Aya; Karino, Genta; Ozawa, Simpei; Tanaka, Ikuko; Honda, Yoshiko; Usui, Setsuo; Kodama, Tohru; Mimura, Koki; Nakamura, Shun; Kunikata, Tetsuya; Yamanouchi, Hideo; et al.
Highlights: Constant light in early life resulted in increasing of alert behaviors in adulthood indicating a disorder in the socio-emotional development of common marmosets. The susceptible period might exist earlier than 3–5 months old. Visualization by multivariate analysis with biological factors supports studies of higher-order psychological function. Abstract: As a diurnal experimental primate, the common marmoset ( Callithrix jacchus ) has recently contributed to numerous kinds of studies of neurobiological psychiatry as an essential pre-clinical model. The marmoset matures sexually within one or two years after birth. Thus, we can observe how the primate learns and develops psycho-cognitive functions through experiences in experimental environment for a much shorter period compared to that of humans. Longer daylight exposure may affect psychological development of children. In our research, we focus on raising marmosets under constant daylight from birth until various ages. In order to quantitatively evaluate the development of higher-ordered psychological functions, we designed a system of socio-behavioral tests and multivariate correlation analysis methods based on principal component analysis. With reference to the call and typical body movement expressed during a particular social context, we statistically inferred the emotional features of the subjects. In the current literature, we review our published results showing increased alert behaviors by constant light, and then, attempted to extend our additional analysis to seek age-dependent susceptibility to constant light. We then present the neurobiological mechanisms with reference to previous research reports. The current review suggests possible existence of a susceptible period earlier than three to five month-old in the environment-induced developmental disorder model, supposedly like attention deficit hyperactive disorders (ADHD) or oppositional defiant disorder (ODD).